2006
DOI: 10.1103/physreve.73.047402
|View full text |Cite
|
Sign up to set email alerts
|

Structure of multispecies charged particles in a quadratic trap

Abstract: Multispecies interacting charged particles in a two-dimensional quadratic trap are studied. The ground-state configurations for different particle and species numbers are obtained by molecular dynamics simulation. It is found that particles with similar mass-to-charge ratio tend to populate a common shell, whose location depends on the particle mass-to-charge ratio, and that the greater the latter, the closer are the particles to the center of the trap. This scaling for the ground-state configuration is indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 25 publications
5
16
0
Order By: Relevance
“…In conclusion, we have determined the minimum energy configurations of a multi-species system of charged particles interacting through a Coulomb repulsive potential confined by isotropic (circular) and anisotropic (elliptical, triangular and square) potentials by means of MD simulation. We have demonstrated that the general rule for particle separation obtained in reference [35] continues to apply within anisotropically confined systems: the larger the mass-to-charge ratio, the closer the particles are to the system center. This rule is found to be independent of the total number of particles, the number of species and the symmetries of the system.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In conclusion, we have determined the minimum energy configurations of a multi-species system of charged particles interacting through a Coulomb repulsive potential confined by isotropic (circular) and anisotropic (elliptical, triangular and square) potentials by means of MD simulation. We have demonstrated that the general rule for particle separation obtained in reference [35] continues to apply within anisotropically confined systems: the larger the mass-to-charge ratio, the closer the particles are to the system center. This rule is found to be independent of the total number of particles, the number of species and the symmetries of the system.…”
Section: Discussionmentioning
confidence: 65%
“…The studies have found that in an isotropic (circular) confinement potential, the particles of different species segregate into different shells, with the particles of the largest (smallest) mass-to-charge ratio tending to populate near to (far away from) the system center [35]. The different particles also become mixed together if they have the same mass-to-charge ratio, although their individual masses and charges [34,35] are different. The investigation performed so far on 2D multi-species systems has been restricted to confinement in an isotropic potential.…”
Section: Introductionmentioning
confidence: 99%
“…The problem considered here can thus serve as a tutorial model for the latter process. Our results should also be relevant to advanced theories of collisions of charged particles in plasmas as well as particle interaction models in molecular dynamics simulation of elongated charged objects, where usually isotropic Debye cutoffs are invoked to avoid divergent integrals [1,3,20] and/or shorten the computation time [21,22].…”
Section: Discussionmentioning
confidence: 92%
“…Recently, there has been a renewed interest in the study of the physical properties of multi-component systems [1][2][3]. The presence of particles with distinct physical properties (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of particles with distinct physical properties (e.g. size, charge, mass) introduces a competition between different scales, which is the reason for the richer phenomenology in such systems [2]. The simplest multi-component system is a binary mixture of two types of particles which, as compared to a mono-disperse system [4][5][6][7][8][9][10], has been shown to exhibit a very rich phase diagram.…”
Section: Introductionmentioning
confidence: 99%